Exploring the Interplay Between Cognitive Ability and Argumentation Skills to Improve Scientific Reasoning in Physics Learning - Dewi Kurniaty; Muslim Muslim; Hera Novia; Rizky Agassy Sihombing (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
This quantitative descriptive–correlational study explored the connection between senior high school students' cognitive abilities and their argumentation skills within the context of physics learning. Conducted at a public high school in Ketapang, West Kalimantan, the research utilized a multiple-choice test based on Bloom's revised taxonomy (C1–C5) to measure cognitive performance. Argumentation skills were evaluated using instruments aligned with Toulmin’s argument pattern (TAP). The findings revealed a decline in students' cognitive performance as task complexity increased, with scores of 78% for remembering, 61.25% for understanding, 45% for applying, 28.75% for analyzing, and 17.50% for evaluating. Similarly, argumentation skills showed a hierarchical pattern: 80% of students could state claims, 65.71% provided evidence, 51.43% explained phenomena, and only 34.29% were able to construct reasoned solutions. A Pearson correlation analysis indicated a strong, positive relationship between the two variables ( r>0.6;p<0.05). These results suggest that a higher level of cognitive ability is linked to stronger scientific argumentation, underscoring the necessity of integrating higher-order thinking skills into physics instruction to improve students' reasoning and scientific discourse.